Identification of Species and Fatty Acid Composition of Microalgae from Raas Beach Sendang Biru Malang and Their Potential as Biodiesel Feedstock - Eli Hendrik Sanjaya; Alifah Novitasari; Parlan Parlan; Laurent Octaviana; Dermawan Afandy; Sitoresmi Prabaningtyas (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2017)
Biodiesel is one of the best renewable energy made from triglycerides. Microalgae has a high lipid content include triglycerides, so it can be used as raw material for biodiesel production. Malang has many of beaches which are potent to become sources of microalgae, several beaches are surrounding Sendang Biru. The aims of this research were to identify the species of microalgae from Raas Beach Sendang Biru, determine their yield of lipid and fatty acid composition, and analyse their potential to became feedstock of biodiesel production. This research consists of five stages: identification of microalgae, cultivation, harvesting, determination of the yield of microalgae lipid by soxhlet extraction method, and analysis of the fatty acid composition of lipid by GC-MS. The results showed that the species of microalgae are dominated by Euglena sp and small amount of Gloeocapsa. The lipid yield of dried microalgae is 7.5% and the fatty acids composition are dodecanoic acid (1.6%), tetradecanoic acid (1.3%), hexadecanoic acid (16.6%), 9,12-octadecadienoic acid (25.2%), 9-octadecenoic acid (29.8%), and octadecanoic acid (6.7%). Based on this results, it can be concluded that the microalgaes from Raas Beach Sendang Biru are potential to become biodiesel feedstock but it still need optimization.